The Role of Technology Acceptance Based on the TAM Model in the Use of Technology in Home Embroidery Businesses - Heniawati, Heniawati; Maulani, Galih Abdul Fatah; Nugraha, Sukma (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
Advances in technology can be applied or utilized to streamline the production process, making it easier for embroidery manufacturers to make a product. One theory about the use of technology that is very influential is the Technology Acceptance Model (TAM). This study aims to identify the role of technology adoption using Technology Acceptance Model (TAM) analysis in the home embroidery industry in Tarunajaya Village, Sukaraja Tasikmalaya District. This type of research is a quantitative approach research with positivistic method and associative descriptive approach. The sample in this study is border entrepreneurs, totaling 168 people, obtained by incidental sampling technique. Data were collected using a questionnaire and then analyzed using product moment correlation. The results of the study found that the Perceived usefulness factor had on the actual system use with a value of 0.000. Perceived case of use on the actual system use with ap value of 0.000. Attitude toward Behavior on actual system use with ap value of 0.000. Intention to use on the actual system use with ap value of 0.000. The conclusion of this research is that the variables that affect the actual system use include Perceived usefulness, Perceived case of use, Attitude toward Behavior, Intention to use.